Sexual Ethics in West African Communitarian: A 21st Century Framework - Ogonegbu, Festus; Ogelenya , Grace (Metafora: Education, Social Sciences and Humanities Journal, 2025)
This paper identifies the increasing tension between traditional African sexual ethics and contemporary human rights discourse in addressing sexual and reproductive challenges across global societies. Such tensions include conflicts over traditional marriage structures, gender roles, sexual identity, and reproductive autonomy amongst others. As a result of these ethical conflicts, human sexuality relationships are not only strained but communitarian wisdom is marginalized as orientations of indigenous sexual ethics are not given attention in human rights policies, the resultant sexual problems and even the solutions provided to address them. The objective of this paper is to show the relevance of African communitarian personhood, through its relational perspective with its attendant sexual values, in addressing certain sexual ethical problems confronting global societies and the world at large. The methods adopted in this paper are philosophical hermeneutics and philosophical analysis in order to understand the orientation of sexual ethics among African communitarian traditions and also to interpret them with the aim of showing their particular and universal relevance, both in African societies and beyond. The paper concludes that a collaborative approach between indigenous sexual values of African communitarianism and the relational aspects of contemporary human rights frameworks would avert individualistic sexual ethics which is a major source of the sexual ethical problems. The approach must be critically rooted in the indigenous communitarian system of African personhood for a more participatory outcome in addressing sexual ethical challenges.